2011
DOI: 10.1038/ng.865
|View full text |Cite
|
Sign up to set email alerts
|

Increased methylation variation in epigenetic domains across cancer types

Abstract: Summary Tumor heterogeneity is a major barrier to effective cancer diagnosis and treatment. We recently identified cancer-specific differentially DNA-methylated regions (cDMRs) in colon cancer, which also distinguish normal tissue types from each other, suggesting that these cDMRs might be generalized across cancer types. Here we show stochastic methylation variation of the same cDMRs, distinguishing cancer from normal, in colon, lung, breast, thyroid, and Wilms tumors, with intermediate variation in adenomas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

69
1,023
4
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 990 publications
(1,106 citation statements)
references
References 41 publications
69
1,023
4
2
Order By: Relevance
“…2d). Of interest, intercellular DNA methylation heterogeneity has been frequently noted in cancer cells in association with reduced global methylation levels 27,28 (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…2d). Of interest, intercellular DNA methylation heterogeneity has been frequently noted in cancer cells in association with reduced global methylation levels 27,28 (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…The findings imply that epigenetic drugs that induce global DNA demethylation and/or the global loss of collaborating histone modifications could adversely affect the functionality of adult progenitor cell populations in patients. Moreover, numerous large blocks with significant hypomethylation were described in colon cancer methylomes (Hansen et al, 2011). These blocks showed increased gene expression variation, which suggested that a further decrease in DNA methylation beyond the normal levels of differentiated cells might induce phenotypic variability (Figure 3).…”
Section: Epigenetic Side Effects Of Global Dna Demethylationmentioning
confidence: 99%
“…These blocks showed increased gene expression variation, which suggested that a further decrease in DNA methylation beyond the normal levels of differentiated cells might induce phenotypic variability (Figure 3). Drugs that induce global DNA hypomethylation could thus promote oncogenic transformation in cancer patients (Hansen et al, 2011), and it appears critical that more specific epigenetic drugs become identified and developed. This might not be achievable through the inhibition of DNA methyltransferases and would therefore require the targeting of other epigenetic factors and pathways.…”
Section: Epigenetic Side Effects Of Global Dna Demethylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Repression of a gene is dependent on the density of the methylation, i.e. how frequently methylated-CpG sequences occur within the gene, and also on the location of the methylation in relation to the promoter region of the gene (Bian et al, 2013;Hsieh, 1994) Epigenetic changes have been linked to many diseases including cardiovascular disease (Webster et al, 2013); as well as colon, lung, breast and thyroid cancer, where large hypomethylated blocks of the genomes have been found (Hansen et al, 2011) and promoter hypermethylation of classic tumour suppressor genes are found. More recently, methylation changes have been associated with fibrotic diseases such as hepatic, pulmonary, renal and cardiac fibrosis (Mann et al, 2010;Rabinovich et al, 2012;Tampe et al, 2014;Xu et al, 2015).…”
Section: Methylationmentioning
confidence: 99%